In pancreatic cancer patients, chemotherapy reshapes the gene expression profile and antigen receptor repertoire of T lymphocytes and enhances their effector response to tumor-associated antigens - Brugiapaglia, Silvia; Bulfamante, Sara; Curcio, Claudia; Arigoni, Maddalena; Calogero, Raffaele; Bonello, Lisa; Genuardi, Elisa; Spadi, Rosella; Satolli, Maria Antonietta; Campra, Donata; Giordano, Daniele; Cappello, Paola; et al. (Frontiers in Immunology, 2024)
Introduction Pancreatic Ductal Adenocarcinoma (PDA) is one of the most aggressive malignancies with a 5-year survival rate of 13%. Less than 20% of patients have a resectable tumor at diagnosis due to the lack of distinctive symptoms and reliable biomarkers. PDA is resistant to chemotherapy (CT) and understanding how to gain an anti-tumor effector response following stimulation is, therefore, critical for setting up an effective immunotherapy. Methods Proliferation, and cytokine release and TCRB repertoire of from PDA patient peripheral T lymphocytes, before and after CT, were analyzed in vitro in response to four tumor-associated antigens (TAA), namely ENO1, FUBP1, GAPDH and K2C8. Transcriptional state of PDA patient PBMC was investigated using RNA-Seq before and after CT. Results CT increased the number of TAA recognized by T lymphocytes, which positively correlated with patient survival, and high IFN-γ production TAA-induced responses were significantly increased after CT. We found that some ENO1-stimulated T cell clonotypes from CT-treated patients were expanded or de-novo induced, and that some clonotypes were reduced or even disappeared after CT. Patients that showed a higher number of effector responses to TAA (high IFN-γ/IL-10 ratio) after CT expressed increased fatty acid-related transcriptional signature. Conversely, patients that showed a higher number of regulatory responses to TAA (low IFN-γ/IL-10 ratio) after CT significantly expressed an increased IRAK1/IL1R axis-related transcriptional signature. Conclusion These data suggest that the expression of fatty acid or IRAK1/IL1Rrelated genes predicts T lymphocyte effector or regulatory responses to TAA in patients that undergo CT. These findings are a springboard to set up precision immunotherapies in PDA based on the TAA vaccination in combination with CT.